A Multi-centre, Randomised, Double-blind, Placebo-controlled Clinical Trial on the Efficacy and Tolerability of GeloMyrtol® forte in Acute Bronchitis - Gillissen, A.; Wittig, Th.; Ehmen, M.; Krezdorn, H. G.; de Mey, C. (Drug Research, 2013)
GeloMyrtol® forte (Myrtol®) is a phytomedicine obtained by distillation from essential oils. The trial was conducted to confirm the efficacy of Myrtol® in the treatment of acute bronchitis.Patients with acute bronchitis and without confounding co-morbidity or co-medication were randomly assigned to treatment with either Myrtol® 300 mg 4 times daily or matched placebo in double-blind, parallel-group fashion. Signs and symptoms were evaluated by the investigator at baseline and after 7, 10 and 14 days of treatment; intake of medication, wellbeing and symptoms were recorded daily by the patient in the patients’ diaries.413 patients were enrolled and randomised (Myrtol®: 202; Placebo: 211); 398 had at least one on-treatment efficacy evaluation (Myrtol®: 196; Placebo: 202). The mean change in coughing fits from D01 (baseline) to D07-D09 (after about one week treatment) was 62.1% (95% CI: 57.6–66.6%) and 49.8% (95% CI: 44.6–55.0%) for treatment with Myrtol® and placebo, respectively (p<0.0001). With Myrtol®, the median time to 50% reduction in coughing fits was statistically significantly shorter and there were more patients without day-time coughing fits; there also were statistically significantly less day-time coughing fits, less difficulty coughing up, less sleep disturbance due to night-time coughing; with Myrtol® there was less symptomatic impairment (composite bronchitis severity score and subscores) and significant more patients had a clinically satisfying response to the investigational treatment.Both treatments were generally well tolerated.Myrtol® is statistically significantly superior to placebo in treating acute bronchitis.
Keywords: acute bronchitis; clinical trial; Myrtol®; GeloMyrtol® forte